Right basal ganglion hypoperfusion in obsessive compulsive disorder patients demonstrated by Tc-99m-HMPAO brain perfusion spect: A controlled study - TOPÇUOĞLU, VOLKAN (TAYLOR & FRANCIS LTD, 2005)
The aim of this study is to demonstrate the regional cerebral blood flows (rCBF) of obsessive-compulsive disorder (OCD) patients compared to controls by using Tc-99m-HMPAO SPECT. Sixteen OCD and seven control subjects were admitted into the study. Yale-Brown Obsessive Compulsive Rating Scale (Y-BOCS), Hamilton Depression Rating Scale (HDRS), and Hamilton Anxiety Rating Scale (HARS) were applied to the patients. The rCBF was found to be decreased in right basal ganglion in OCD patients. The right basal ganglion rCBF was negatively correlated with Y-BOCS total and compulsion scores. The left thalamus rCBF was negatively correlated with Y-BOCS obsession score. Right and left cingulate rCBF were negatively correlated with HDRS score. The results indicating hypoperfusion in right basal ganglion in OCD patients support previous findings about dysfunction of frontal-subcortical circuits in this disorder.
Keywords: basal ganglia; frontal subcortical circuits; hypoperfusion; obsessive-compulsive disorder; SPECTY-BOCS; CEREBRAL-BLOOD-FLOW; EMISSION COMPUTERIZED-TOMOGRAPHY; CAUDATE-NUCLEUS; CIRCUITS